Voter Preferences Reflect a Competition Between Policy and Identity - Jenke, Libby; Huettel, Scott A. (Frontiers in Psychology, 2020)
Canonical rational choice models of voter preferences assume that voters select candidates whose policy positions most closely match their own. Yet, much of the electorate often appears to prioritize identity variables (e.g., social categories, group membership) over policy considerations. Here, we report an empirical test of policy-identity interactions using surveys of likely voters conducted in the 24 hours before the 2016 US presidential election and the 2018 US senatorial elections. Each respondent indicated not only their policy preferences but also key social identities and how those identities would be reinforced by voting. We observed striking evidence for a competition between policy and identity: For voters who exhibited the maximal effects of identity, policy positions were essentially irrelevant to their candidate preferences. These results account for dissociations between voters’ stated policy preferences and their voting behavior, while linking empirical observations of political behavior to new models derived from psychology and neuroscience.